Establishment of somatic embryogenesis regeneration system and transcriptome analysis of early somatic embryogenesis in litchi - Yaqi Qin; Bo Zhang; Shiqian Wang; Wuyan Guo; Zhike Zhang; Yonghua Qin; Jietang Zhao; Guibing Hu (Horticultural Plant Journal)
Litchi chinensis Sonn. is an important economic fruit tree in tropical and subtropical regions. Regrettably, the efficiency of plant regeneration via somatic embryogenesis in litchi is typically low due to the poor conversion of embryos to plants. The purpose of this study was to establish a regeneration system via somatic embryogenesis from immature embryos explants in ‘Heiye’ cultivar of litchi. Our results demonstrated that MS medium supplemented with 2.0 mg L−1 2,4-D was optimal for callus induction. For somatic embryo (SE) induction, MS medium containing 0.5 g L−1 activated charcoal (AC) was the most effective, while the use of zeatin (ZT) and thidiazuron (TDZ) resulted in abnormal somatic embryos. The rooting and regeneration rate of 2.15% and 17.5%, respectively, were achieved using MS medium supplemented with 0.5 g L−1 AC. Furthermore, transcriptome analysis was performed on embryogenic callus (EC), globular embryo (GE), and heart embryo (HE) to explore the molecular mechanisms of early somatic embryogenesis. 2,587 common differentially expressed genes (DEGs) between EC_vs_GE and EC_vs_HE were identified, and the expression patterns of these common DEGs were separated into twelve major clusters. GO annotation and KEGG pathway analysis revealed that these common DEGs were implicated in plant hormone signal transduction, auxin-activated signaling pathway, and other biological processes. Additionally, differentially expressed transcription factors were identified, and the function of LcBBM2 which is specifically highly expressed during early somatic embryogenesis was verified. Overexpression of LcBBM2 in tomato promotes callus and shoot formation. Therefore, this study can provide a theoretical basis and technical support for genetic breeding improvement of litchi.